Perilaku Bullying Mahasiswa Kesehatan - Wardani, Lingga Kusuma; Fajriansyah, Fajriansyah (Journal Of Nursing Practice, 2017)
Bullying behavior is an act of intimidation by a strong side against a weak side. Bullying behavior can be grouped into four categories: physical bullying, verbal bullying, social bullying and cyber bullying. Students are in the transition from adolescence to adult. The purpose of this study is to explore the behavior of bullying by healthstudents.The design of this research is qualitative with case study approach. Using the Snowball Sampling technique obtained samplemostly students of Nurse Education Program Studyof the number 4 informants. Data collection conductedindept interview, the result was analyzed using inductive thinking process.Data analyzedshowed four themes of knowledge deficits, bullying awareness, repetitive behavior, and self impact.The results showed that students know what is bullying behavior, but bullying University still done by intimidating verbally and with physical strength